Roads & SDGs, tradeoffs and synergies: learning from Brazil's Amazon in distinguishing frontiers - Alexander Pfaff; Juan Robalino; Eustáquio J. Reis; Robert Walker; Stephen Perz; William Laurance; Claudio Bohrer; Steven Aldrich; Eugenio Arima; Marcellus Caldas; Katherine Kirby (Kiel Institute for the World Economy (IfW), 2017)
To inform the search for SDG synergies in infrastructure provision, and to reduce SDG tradeoffs, the authors show that road impacts on Brazilian Amazon forests have varied significantly across settings. Forest loss varied predictably with prior development - both prior roads and prior deforestation - and in a spatial pattern suggesting a synergy between forests and urban growth in such frontiers. Examining multiple roads investments, the authors estimate impact for settings of high, medium and low prior roads and deforestation. Census-tract observations are numerous for each setting and reveal a pattern, not consistent with endogeneity, that confirms our predictions for this kind of frontier. Impacts are: low after relatively high prior development; larger for medium prior development, at the forest margin; then low again for low prior development. For the latter setting, the authors note that in such isolated areas, interactions with conservation policies influence forest impacts over time. These Amazonian results suggest "SDG strategic" locations of infrastructure, an idea they suggest for other frontiers while highlighting differences in those frontiers and their SDG opportunities.
Keywords: O12; O13; H23; H41; Q23; Q24; Q56; 330; deforestation; roads; infrastructure; climate change; biodiversity; Brazil